2009
DOI: 10.1016/j.placenta.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and S Phase of the Cell Cycle in BeWo Trophoblastic and HeLa Cells are Differentially Modulated by Toxoplasma gondii Strain Types

Abstract: Transplacental transmission of Toxoplasma gondii causes congenital toxoplasmosis, one of the most severe forms of infection. The ability of the parasite to survive intracellularly largely depends on the blocking of different proapoptotic signaling cascades of the host cells. During pregnancy, however, alterations in the incidence of apoptosis are associated with abnormal placental morphology and function. The aim of this study was to evaluate the incidence of apoptosis and cell proliferation in trophoblastic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
0
21
0
6
Order By: Relevance
“…Another study reported that BeWo choriocarcinoma cells went into apoptosis after infection with type II rather than type I strains. In this case, host cell death versus parasite death might reflect differential strain abilities to infect the placenta with varying degrees of virulence [21]. …”
Section: Toxoplasma Gondii Genotypes Differentially Transmit Through mentioning
confidence: 99%
“…Another study reported that BeWo choriocarcinoma cells went into apoptosis after infection with type II rather than type I strains. In this case, host cell death versus parasite death might reflect differential strain abilities to infect the placenta with varying degrees of virulence [21]. …”
Section: Toxoplasma Gondii Genotypes Differentially Transmit Through mentioning
confidence: 99%
“…Interestingly, the success of these strategies in murine hosts appears to vary dramatically by parasite strain. Strain-dependence has been observed for a range of phenotypes including blockade of host apoptosis [6], evasion of p47 GTPase-mediated killing [7], production of IL-12 [8], intersection of MAPK signaling [9], induction of NF-κB signaling [10], and induction and sustenance of JAK/STAT signaling [11]. It is therefore not surprising that where specific parasite effectors underlying these phenotypes have been identified and characterized, they are either highly polymorphic between different parasite strains [11], [12], [13] and/or differentially expressed between strains [9], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, parasites may invade at the decidua-EVT interface, which occupies less than 5% of the maternal-fetal interface (Fig. 1B) (10).Almost all experimental T. gondii infections of the placenta have been performed in mice (6,24,34,54,63), sheep (16), or isolated trophoblast cells (4,7,34,52,55,56). However, none of these models accurately represent the architecture of the human placenta (reviewed in references 43 and 46).…”
mentioning
confidence: 99%